Tingkat ke Efektivan Metode Tradisional Massage Dalam Menurunkan Kelelahan Guru PJOK Madrasah Ibtidaiyah Kecamatan Tayu Kabupaten Pati - Pangesti Adji, Tito (Aisyah Journal Of Physical Education (AJoPE) e-ISSN : 3046-790X, 2024)
The aim of this research is to find out whether traditional massage is useful in reducing the level of fatigue of PJOK teachers. Therefore, it is hoped that this effort can significantly improve the performance and welfare of PJOK teachers in various industrial sectors. With a one group experimental design, this research is quasi-experimental in nature. From 20 to 22 June 2024, this research was conducted in Mukim Tayu, Pati Regency. The research population was 14 PJOK Madrasah Ibtidaiyah teachers in Tayu District who experienced fatigue. To determine the number of samples with the total samples obtained, this research used a total sampling technique. Paired t-test analysis is the data analysis method used in this research. Based on analysis data with a significance value of 0.000 on the traditional massage hypothesis test data on fatigue therapy, research findings show that traditional massage methods can reduce fatigue levels. A value of 0.000<0.05 based on these findings indicates that the pre-test and post-test data are significantly different. With a p value <0.05, the study concluded that traditional massage techniques can reduce fatigue levels significantly.